(untitled) (Bangladesh Journal of Neurosurgery, 2026)
Background: Postoperative facial nerve palsy after CPA vestibular schwannoma surgery via the retro-sigmoid retro-mastoid sub-occipital route is a well-recognized complication. Its occurrence depends on tumor characteristics, surgical technique, and intraoperative nerve preservation strategies. Advances in microsurgical dissection and intraoperative neuro-monitoring have improved outcomes, but some risk remains inherent due to the complex anatomy of the CPA region. Presenting symptoms, treatment considerations, and postoperative facial nerve palsy are strongly related to the extension of vestibular schwannomas (VS). Ongoing research aims to optimize surgical techniques and postoperative management to improve facial nerve preservation and patient outcomes. Methods: The study included 130 patients diagnosed with cerebello-pontine angle vestibular schwannoma who underwent surgical resection via the retro-sigmoid retro-mastoid sub-occipital approach at our institution between January 2017 and May 2022. All surgeries were performed using this posterior fossa route aiming for maximal tumor removal while aiming to preserve nerve function. Postoperative facial nerve function was assessed using the House-Brackmann (HB) grading system at specified intervals to evaluate the degree of facial palsy and recovery. Hearing function was evaluated pre- and post-operatively using pure tone audiometry (PTA). Data collected included patient demographics, tumor size and location, intraoperative findings, and postoperative nerve status. The goal was to analyze the incidence, severity, and recovery patterns of facial nerve palsy following this surgical approach, providing insights into nerve preservation and surgical outcomes. Results: Most patients had large tumors and had no useful hearing (75.38%), had disabling cerebellar ataxia (84.61%) and presented with features of raised intracranial pressure (46.15%). Complete tumor excision was carried out 92.30% and anatomical preservation of facial nerve was achieved in 87.50% cases. Hearing preservation was achieved in eight (6.2%) patients. Conclusions: Postoperative facial nerve palsy is a significant and common complication associated with the surgical removal of vestibular schwannomas located in the cerebello-pontine angle (CPA). Due to anatomical relationship, surgical manipulation or tumor dissection can put the facial nerve at risk of injury. Facial nerve palsy can range from mild weakness (House-Brackmann grade II) to complete paralysis (grade VI), affecting facial expression, eyelid closure, speech, and oral competence, thereby impacting the patient’s quality of life. The incidence of postoperative facial nerve dysfunction varies depending on tumor size, surgical technique, and surgeon experience, but it remains a key concern in vestibular schwannoma surgeries. Hearing preservation is difficult in larger tumors. Primary microsurgical resection is an appropriate management option for large VS. In our experience, this goal can be achieved safely and successfully by using the retromastoid retrosigmoid sub-occipital approach. Bang. J Neurosurgery 2025; 14(2): 118-125